A cycad's non‐saturating response to carbon dioxide enrichment indicates Cenozoic carbon limitation in pre‐historic plants. (27th February 2018) - Nackley, Lloyd L.; Midgley, Guy F.; Bösenberg, Jacques de Wet; Donaldson, John S.
Abstract: Cycads were a dominant plant functional type during the Mesozoic Era when atmospheric carbon dioxide [CO2 ] greatly exceeded current conditions. Cycads, now rare and endangered, are slow‐growing perennial gymnosperms that develop carbon‐rich structural biomass, such as sclerophyllous leaves, dense stems and massive reproductive cones. Is cycad carbon partitioning to specific organs a constraint of their high [CO2 ] evolutionary history (CO2 legacy hypothesis, CLH)? To explore changes in cycad growth, carbon partitioning and assimilation responses that could be expected during the CO2 depletion of the Cenozoic Era, individuals of the cycad species Encephalartos villosus plants were grown at four CO2 levels: 400, 550, 750 and 1000 μmol mol −1 . The CLH predicts that cycad biomass and growth rates would increase in elevated [CO2 ] due to increased net assimilation rates, and that carbon‐dense structures would provide sufficient carbohydrate sinks to prevent photosynthetic down‐regulation even under super‐ambient [CO2 ] of 1000 μmol mol −1 . Both hypotheses were confirmed, though the latter less strongly. Plant relative growth rates increased 23% and biomass accumulation increased 65% in 1000 μmol mol −1 relative to 400 μmol mol −1 treatment groups. Mean net assimilation rates increased 130% at 1000 μmol mol −1 relative to 400 μmol mol −1 CO2, though there was some down‐regulation of maximum rate of carboxylation (Vcmax ). Assimilation rates, relative growth rates, biomass and mean leaf sugar content were linearly related to [CO2 ] over the entire experimental range. Photosynthesis appears to be regulated by stomata at low CO2 levels and by non‐stomatal (i.e. biochemical limitations) at greater concentrations. In general, our results suggest that growth and physiological performance of cycads have been severely compromised by declining [CO2 ] during the Cenozoic Era, possibly contributing to the current rare and endangered status of this functional type.